Aviation Entrepreneur Model (AEM) in Malaysia: A Review - Abdul Kadir, Suhaila; Muhamad Saufi Che Rusuli (European Journal of Multidisciplinary Studies, 2016)
Studies in the literature have discussed on many of the success factors of small and medium enterprises. However, Aviation Entrepreneur has been given less attention by previous researchers. In present, Aviation Entrepreneur plays an important role in determining the success and Aviation Entrepreneur inculcating “wholesome” Aviation Entrepreneurs. The concept of this review is based on the Aviation Entrepreneur Model factors that contribute to the successful aviation entrepreneur such as traits, behavior, skills and self-efficacy. This study will provide a guideline to some parties involved either the government or private agencies like Small Medium Enterprises (SME), Majlis Amanah Rakyat (MARA), SMIDEC, FMM and PUNB for the purpose of developing small businesses so that Aviation Entrepreneurs can be globally competitive.